Schistosoma japonicum Infection Promotes the Response of Tfh Cells Through Down-Regulation of Caspase-3–Mediating Apoptosis - Yang, Quan; Qu, Jiale; Jin, Chenxi; Feng, Yuanfa; Xie, Shihao; Zhu, Jinxin; Liu, Gaoshen; Xie, Hongyan; Qiu, Huaina; Qi, Yanwei; Mu, Jianbing; Huang, Jun (Frontiers in Immunology, 2019)
CD4+ T follicular helper (Tfh) cells, a new subset of immune cells, have been demonstrated to be involved in granulomatous responses to Schistosoma japonicum (S. japonicum) infection. However, the role and underlying mechanisms of Tfh cell aggregation in S. japonicum infection remain incompletely understood. In this study, we provide evidence that S. japonicum infection enhances the accumulation of Tfh cells in the spleen, lymph nodes, and peripheral blood of C57BL/6 mice. Infection-induced Tfh cells exhibited more potent effects directly on B cell responses than the control Tfh cells (P < 0.05). Furthermore, reduced apoptosis of Tfh cells was found both in S. japonicum infected mice and in soluble egg antigen (SEA) treated Tfh cells (P < 0.05). Mechanistic studies reveal that caspase-3 is the primary drivers of down-regulated apoptotic Tfh cell death in S. japonicum infection. In summary, this study demonstrates that Tfh cell accumulation might have an impact on the generation of immune responses in S. japonicum infection, and caspase-3 signaling mediated apoptosis down-regulation might responsible for the accumulation of Tfh cell in this course.